Monica Antonello, Communication Strategies in English as a Lingua Franca Transcultural Communication, Newcastle upon Tyne: Cambridge Scholars Publishing, 2023, 330 p. - MIHELE, Roxana (Studia Universitatis Babeș-Bolyai Philologia, 2024)
In an increasingly globalized economy and cosmopolitan society, teaching and training tomorrow’s specialists brings new challenges for the (foreign) language teachers. ESP (English for Specialized Purposes) tutors in particular need to pay attention to the way they prepare their students and improve upon their foreign language skills, so that young graduates can easily find insertion in the labor market. In some specific domains, such as Tourism, where interaction with both natives and foreign speakers of English can be a regular if not daily occurrence, mastering an average level of English and demonstrating some degree of intercultural communication competency may no longer be enough. Which specific variety of English should students today know and be expected to use? Is the Native Speaker standard still the golden model foreign users of English are supposed to emulate? What is the difference between having ICC (Intercultural Communication Competence) training and mastering Transcultural Competence? Should English tutors focus on teaching ELF (English as a Lingua Franca) or ESL (English as a Second Language)? What methodological and didactic implications will this have for the ELT (English Language Teaching) modules future teachers are to follow? Monica Antonello’s 2023 book, Communication Strategies in English as a Lingua Franca Transcultural Communication, provides ample and well-informed answers to these questions, bringing forth a new perspective on the specific nature of the (verbal) interaction between speakers when English is just a mere medium of communication. The author also proposes English teachers a revaluation of the role traditional Standard English model and Native Speaker proficiency goal should play nowadays in a world where most of the time, and in most contexts, interlocutors do not share the same linguistic or cultural background, nonetheless they still use English as a common currency for communication and mediation.